Why comply? Farmer motivations and barriers in cannabis agriculture. (August 2021) - Bodwitch, Hekia; Polson, Michael; Biber, Eric; Hickey, Gordon M.; Butsic, Van
Abstract: Cannabis legalization is spreading rapidly. In California, as the plant transitions from an illegal drug to agricultural product, regulations have been implemented to manage its production and associated environmental impacts. Yet, at the early stages of this process, many of the state's cannabis farmers continue to operate illicitly. This study examines why some cannabis farmers are engaging in the state's licensing initiative while others are not. Through an anonymous survey of cannabis farmers in California, we analyzed socio-normative and cost-related factors influencing farmers' decisions to participate in legal markets, or not. Approximately one third of the 362 cannabis farmers who completed the survey reported that they had never applied for a license. These non-compliant farmers were likely to be smaller cultivators who grew cannabis as part of a diversified livelihood strategy. Farmers' non-compliance was primarily attributed to an inability to overcome barriers to participation. These included not only financial barriers but also administrative and psychological ones, all of which disproportionately affect farmers with fewer resources. Socio-normative factors, including pressure from neighbors and perspectives on the benefits of environmental regulations, were not found to motivate non-compliance. As a result, policy efforts to mitigate the administrative burdens of compliance, such as streamlining permitting processes, extending agricultural support services, and supporting farmer collectives, warrant further attention to enhance compliance, public safety, environmental outcomes, and rural development in cannabis cultivating communities. Reforms to promote compliance, particularly among smaller farmers, may prevent the kinds of industrial consolidation seen in agricultural and in other governmental efforts to regulate informal resource use and trade. Highlights: California's cannabis policies hold farmers to high environmental standards. Despite legalization many cannabis farmers engage in illicit, informal economies. A survey of 362 cannabis farmers examined compliance motivations and barriers. Compliance costs and administrative burdens were primary barriers to compliance. These costs exclude smaller farms from legal markets.